Investigation of Grouted Coupler Connection Details for Accelerated Bridge Construction. Issue 8 (August 2021) - Phares, Brent; Lee, Yoon-Si; Hosteng, Travis K.; Nelson, Jim
This paper presents a laboratory investigation on the performance of grouted rebar couplers with the connection details similar to those utilized on the precast concrete elements of the Keg Creek Bridge on US 6 in Iowa. The testing program consisted of a series of static load tests, a fatigue test, and evaluation of the chloride penetration resistance of laboratory specimens. The goal of this testing was to evaluate the ability of the grouted rebar couplers to develop flexural capacity at the joint between the precast elements as well as the durability of the connection. For structural load testing, seven full-scale specimens, each with #14 epoxy-coated rebars spliced by epoxy-coated grouted couplers, were fabricated and tested in three different loading cases: four-point bending, axial tension plus bending, and a cyclic test of the system in bending. The static load testing demonstrated that the applied axial load had a minimal effect on the formation of cracks and overall performance of the connection. When ultra-high performance concrete was used as a bedding grout, the initiation of crack was slightly delayed but no considerable improvement was observed in the magnitude of the crack width during loading or the crack closure on unloading. The results of the seventh specimen, tested in fatigue to 1 million cycles, showed little global displacement and crack width throughout the test, neither of which expanded measurably. No evidence of moisture or chloride penetration was detected at the grouted joint during the 6-month monitoring.